4C SKILLS OF THE 21ST CENTURY: THEIR NATURE AND IMPORTANCE IN PRIMARY SCHOOL LEARNING - Robi Agape Barus (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
21st century skills absolutely must be taught at all levels of education, especially elementary schools, because students have experienced very fast changing times. Elementary school students are automatically involved in becoming part of 21st century society. Therefore, 21st century 4C skills, namely Critical Thinking and Problem Solving, Communication, Collaboration, and Creativity and innovation should be taught at all levels of elementary school classes according to the development and needs of students . The aim of the study is to describe the nature of 21st century skills and the importance of their application in elementary schools. The research method used is literature study. The data sources in this study were examined from various reading sources such as books and journal articles. This method is carried out so that this journal article can provide relevant and reliable information based on data sources and provide a clear picture of 21st Century 4C skills in elementary schools. The results of this study indicate that teaching 21st century skills is a necessity for every school to form skilled students in 21st century society. The learning objectives are so that students are familiar with good communication, cooperate in a compact manner, are critical of problems and are able to solve them, and are critical and innovative in their work produce new goods.